The utility of pectoral drain in patients undergoing modified radical mastectomy-an observational study - Kumar, Yogesh; Kumar, Ashok; Singh, Vineet; Pakhriya, Shobha (International Surgery Journal, 2017)
Background: Breast cancer is one of the most common malignancies in female and in developing countries majority of them present in locally advanced stages. Modified radical mastectomy (MRM) is the main surgical management & axillary drain is deployed to tackle the leaking axillary lymphatics. However, if at all the pectoral area between the skin flaps and pectoral muscles requires drainage can be contested since the skin flaps are snugly approximated to the chest wall obliterating any potential space. The study is conducted to evaluate the output of pectoral drain & axillary drain in patients of MRM. Methods: This is a prospective study of 120 consecutive patients over a 2-years period who presented with breast cancer and undergone MRM in a teaching hospital. Two separate drains equal in all parameters were inserted in axilla and pectoral area and the collection in these drains studied post operatively. Results: The contribution of pectoral drain to total drain output was only 7.97%, while the axillary drain contribution was 92.03% in total drain output. So, the contribution from the pectoral drain was statistically insignificant (p=<0.001). Conclusions: MRM can be performed without drainage at the pectoral area.